Memórias docentes sobre o início da UNESP em Presidente Prudente: busca por meio de imagens (1975-1980) - Oliveira, Édison Trombeta de [UNESP] (2014)
This research, which is linked to the study line Formative process, difference and values, from the Postgraduate Program in Education, has as a main concern the idea that having a notion of the history of educational institution is an elemental factor to understand it as it is and problematize about its future. Conflicts that occurred in institutions can indicate its fundamental principles and assist in building the sense of belonging of its subjects. Thus, this dissertation aims at the historical reconstruction of the early (installation, permanence and consequences) of Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP) in Presidente Prudente-SP, which occurred in 1976. Previously, the university campus was named Faculdade de Filosofia, Ciências e Letras (FFCL), a Higher Education Institute Isolated (IIES, its Portuguese acronym), and came to possess Pedagogy, Social Sciences, Bachelor of Science, Geography and Mathematics courses. After installation of UNESP only the last two courses remained, some teachers were dismissed and others transferred. In order to get memories about this fact, we used the Oral History procedements combined with images of that period, then in a procedure known as Evocative Image of Memory. A specific objective of this research was to ask questions about this procedure. Nine teachers were listened, one could conclude that while most consider the process as traumatic, some saw on it an opportunity for learning and growth...